Independent effects of 2-D and 3-D locations of stimuli in a 3-D display on response speed in a Simon task - Umemura, Hiroyuki (Frontiers in Psychology, 2015)
The Simon Effect is a phenomenon in which reaction times are usually faster when the stimulus location and the response correspond, even if the stimulus location is irrelevant to the task. Recent studies have demonstrated the Simon effect in a three-dimensional (3-D) display. The present study examined whether two-dimensional (2-D) and 3-D locations simultaneously affected the Simon effect for stimuli in which a target and fixation were located on the same plane (ground or ceiling) at different 3-D depths, and the perspective effect produced a difference in the 2-D vertical location of the target stimulus relative to the fixation. The presence of the ground and ceiling plane was controlled to examine the contextual effects of background. The results showed that the 2-D vertical location and 3-D depth simultaneously affected the speed of responses, and they did not interact. The presence of the background did not affect the magnitude of either the 2-D or the 3-D Simon effect. These results suggest that 2-D vertical location and 3-D depth are coded simultaneously and independently, and both affect response selection in which 2-D and 3-D representations overlap.